The Relationship of Logistic Technology in Supply Chain Management on the Customer Relations - Zainal, Nadia; Raja Mohd Rasi, Raja Zuraidah (Research in Management of Technology and Business, 2021)
Logistic technologies are very important due to the development of the economy that keeps on rising. When there is great information being provided, it showed that it is good management. Information technology has a mission in which to be better in managing the performance of businesses. For example, if a company make an investment in enterprise resource planning, it is a good decision because there are many benefits in this system which we can see through production, finance, marketing and it is computer-assisted business management. Logistic technologies became important in a company in order to keep relevant in the market and managing customer relations. According to (Fadiah et al., 2017), logistics service capability could be defined as the ability of logistics firms to create and apply all the resources in a good way to satisfy the customers. The objectives of this research are to identify the level of logistic technology used in the supply chain company and to determine the relationship between logistic technology and customer relations. The method used in this research is using Google Form that has been distributed to the employees of supply chain companies through an online survey. In this study, the researcher found that there is a significant relationship between logistic technologies on customer relations. It can be concluded that logistic technologies are very crucial in this current economy.